Absolute Numerosity Discrimination as a Case Study in Comparative Vertebrate Intelligence - Nieder, Andreas (Frontiers in Psychology, 2020)
In comparative psychology, one of the great challenges to contrasting the cognitive capabilities of diverse species is the exact comparability of behavioral data. Usually, available data are collected by different laboratories under different protocols that prevent precise comparison. This article explores one of the rare cases in which three vertebrate species (humans, macaques, and crows) experienced identical conditions during the investigation of a core cognitive capability – the abstract categorization of absolute numerical quantity. The analysis shows that not all vertebrates are able to discriminate absolute numerosity. Additionally, systematic differences in judgment accuracy exist among those vertebrates that can make elaborate numerosity judgments. These results demonstrate that Macphail’s Null Hypotheses - which suggests that all nonhuman vertebrates are qualitatively and quantitatively of equal intelligence - is untenable.